Institutionalizing Conscience: Beyond Agency and Individuality...Wasserman JA, Brummett A, Navin MC. A Defense of Institutional Conscience Rights for Secular Hospitals: Philosophical Justifications and Practical Applications. American Journal of Bioethics. 2026;26(7):45-58. - Lamb, Christina (American Journal of Bioethics, 2026)
The article critically examines the concept of institutional conscience (IC) in healthcare ethics, emphasizing that conscience is fundamentally an individual moral capacity grounded in agency, freedom, and responsibility rather than a collective institutional attribute. It argues that policies on institutional conscience must carefully distinguish between individual and collective moral commitments to avoid incoherence and ethical confusion, especially in pluralistic healthcare settings. While faith-based institutions often have more cohesive conscience protections due to shared normative commitments, secular organizations require a robust philosophical framework to support individual conscience amid changing social norms. The article highlights the need for policies that foster moral discourse and respect individual conscience without merely appeasing institutional tensions, suggesting that protecting individual conscience should take precedence when conflicts arise.